Gender and the Internet - Hiroshi Ono; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2002)
This article examines whether there are differences in men's and women's use of the Internet and whether any such gender gaps have changed in recent years. The authors use data from several surveys during the period 1997 to 2001 to show trends in Internet usage and to estimate regression models of Internet usage that control for individuals' socioeconomic characteristics. They find that women were significantly less likely than men to use the Internet at all in the mid-1990s, but the gender gap in usage disappeared by 2000. However, women continue to be less frequent and less intense users of the Internet. The results suggest that there is little reason for concern about sex inequalities in Internet access and usage now, but gender differences in frequency and intensity of Internet usage remain.
Keywords: 330; Internet; Computers